Geography B - Owen, Andy; Brown, Alan; Davis, Val; Digby, Bob; Leeder, Andy (Dynamic learning, 2020)
Develop your students' subject knowledge and skills using this second edition Eduqas GCSE (9-1) Geography B Student book. Featuring new case studies, practice questions and clear presentation of key terms, this thoroughly revised edition provides students with the up-to-date knowledge they need to succeed at GCSE. - Enhances students' subject knowledge, critical thinking and problem-solving skills using clear explanations of geographical issues, brought to life through an exciting, enquiry-based approach - Teaches students how to interpret, analyse and evaluate geographical information through a range of progressive, skills-building activities that use real-place data, maps and photographs - Boosts candidates' confidence approaching examination by providing opportunities for practice for each assessed theme - Highlights possible fieldwork projects and contains guidance on carrying out investigations that meet the changed assessment requirements.